What can Motorsport do to automotive industry development - Santo, Rodrigo Ferreira (2017)
Ever after the appearance of mankind, evolution has taken place, which occurred thanks to ground breaking inventions, and with those inventions, came innovations. Since the invention of the car itself, there has always been a necessity to make it better – faster, more reliable and efficient and that translated in constant innovations appearing in the automotive industry. There are countless examples of innovation in the automotive industry dating as back as to the beginning of the 20th century and from the moment the car was invented that comparing different cars’ performances has become kind of a necessity. At the moment comparing became competition motorsport was born. This sort of competition and sport became the “vehicle” where major innovation in the automotive takes place. Allowing manufacturers to test new technologies at the harshest conditions let motorsport be the somewhat of the showcase of automotive engineering. The analysis of some of these technologies adopted in road cars that were meant to be in a racing car allowed to conclude what can motorsports do for the automotive industry innovation.